The Intrinsic Chemistry of Melanin Modifies Radically Current Concepts about the Bioenergetics of Photosynthesis: A Review - Herrera, Arturo Solís (Recent Research Advances in Biology Vol. 7, 2021)
Bioenergetics, in biochemistry, is defined as the study of the continuously energy transformation in biological systems. It is considered a branch of cell biology, biochemistry, and biophysics. Bioenergetics can be defined as field in biochemistry that concerns energy flow through living organisms and systems. So far, respiration, that is considered necessary for the survival of plants and animals, supposedly, cell uses oxygen to break down molecules, and during that process, complex organics molecules are broken down into simpler inorganic compounds and thus energy is released. The complex organic molecules and oxygen, needed for respiration and therefore for life, are replenished through the process of photosynthesis. In nature, the only continuously available source of radiant energy is sunlight. Thereby, in photosynthesis, this radiant energy is converted into chemical energy, with oxygen produced as by-product. Theoretically, only chlorophyll- containing plants and relative pigments, are able to convert solar energy into photochemical energy. However, our finding about the intrinsic property of melanin to transform visible and invisible light into chemical energy through the dissociation of the water molecule, breaks old paradigms creating new ones.